Implementation Of E-Commerce At Mega Komputer Store Using The Crm Method - Tiara Pramuni Suci; Venny Novita S Sari; Ricky Zulfiandry (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The development of information technology has driven the transformation of conventional businesses toward digital systems, one of which is through the implementation of e-commerce. Mega Komputer, as a provider of computer products, faces challenges in improving customer loyalty and service effectiveness. This study aims to implement an e-commerce system integrated with Customer Relationship Management (CRM) methods to enhance service quality, strengthen customer relationships, and increase sales. The research method used is a case study with a CRM system implementation approach in Mega Komputer store’s e-commerce platform. Data was obtained through observation, interviews, and documentation. The results show that the implementation of CRM-based e-commerce can improve customer interaction and satisfaction through more effective customer data management, service personalization, and more intensive communication. Additionally, this system assists the store in customer segmentation and targeted marketing strategies. Thus, the implementation of e-commerce using CRM methods significantly contributes to improve the business performance of Mega Komputer Store in the digital era.